Optimizing Digital Content Management to Increase the Effectiveness of Fajarcirebon.com's Online Media - Rattanaya, Kayla; Aminullah, Raynaldi; Imawan, Khaerudin; Rahmayanti, Rahmayanti (ann4publisher@gmail.com, 2025)
Abstract The advancement of digital media demands content management that not only delivers information but also aligns with the increasingly diverse needs, interests, and preferences of users. In an era where information is easily and rapidly accessible, audiences play a more active role in selecting content that meets their specific needs. This study aims to evaluate the effectiveness of digital content on online media by applying the Uses and Gratifications Theory, which views audiences as active subjects in selecting, utilizing, and responding to media to fulfill specific purposes such as acquiring information, entertainment, or engaging in social interaction. Through a conceptual approach to digital content practices across various platforms, this study identifies three main issues on the online media website fajarcirebon.com: the absence of clearly presented key points that aid comprehension, the lack of external links that support informational credibility, and the suboptimal use of images that affects visual appeal and content reach. This article proposes solutions including the development of key points, the addition of external links, and the optimization of visuals to enhance user engagement and overall content effectiveness. The findings are expected to serve as a reference for online media in designing content strategies that are more adaptive and responsive to the current needs of digital audiences.